Penentuan Kebutuhan Tenaga Kerja Optimal Produksi Arm Tie Band dengan Metode Stopwatch Time Study dan Workload Analysis (Studi Kasus: PT. XYZ) - Allan Febriyanto; Handy Febri Satoto (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT. XYZ is known as a manufacturing company in East Java engaged in supporting power grid construction and producing arm tie bands as one of the supporting components for electrical installations. This study was conducted to establish working time standards and the need for effective labor using stopwatch time study and workload analysis (WLA) methods. Data collection was carried out through direct observation 30 times on each work element during production operational hours. The data was then analyzed using data uniformity and sufficiency testing, performance rating assessment, normal time calculation, relaxation factor, standard/standard time, and standard output. The results showed that the total standard production time of arm tie bands was 193.64 seconds or the equivalent of 3.23 minutes. In addition, bottlenecks were found in the process of installing plate wire because it has the lowest output capacity compared to other work elements. Based on the results of the workload analysis, the ideal number of workers needed by the company is 9 workers, so it is necessary to add 1 worker to the plate wire installation section to improve the balance of the workload and the efficiency of the production process.